DEVELOPMENT OF KNIFE EYES ON THE MAKING PROCESS OF ORGANIC BURNING PROCESS OF 7 LITERS FOR UMKM - Ahmad Yunus Nasution (Talenta Publisher, 2018)
The planning and design of the blades mixer for the organic slurry dough mixer is the application of the sciences obtained in real college. The main purpose of making blades mixer for this slurry dough mixer is to get an effective, efficient blades mixer design and higher quality organic slurry. With the making of this blades mixer, it is expected to contribute positively in the middle industry engaged in the food industry. The author designed several forms of modeling of blades mixer capable of stirring the organic pulp mixture with a capacity of 7 liters. The blades mixer are planned to use 304 steinless steel Austenitic material. For a planned blades mixer rotation of 35 rpm, and to achieve such a large rotation, pulleys and gearboxes (reducers) take an important role to achieve the planned rotation. The treatment carried out for this organic slurry dough mixer can be in the form of planned and unplanned treatments. With this report, it is expected to be able to add knowledge in the field of engineering.